Model Tuntutan Pekerjaan dan Sumber Daya Pekerjaan: Sebuah Tinjauan Literatur - Puspita Puji Rahayu (JUDICIOUS, 2021)
Work characteristics are important aspects of work that can have an impact on employee welfare. The characteristics of work are divided into two, namely job demand and job resources. The JD-R model is a refinement of two previously developed job stress models, namely the demands-control model (DCM) (Karasek, 1979) and the effort-reward imbalance model (ERI) (Siegrist, 1996). This study uses a literature review approach. It is hoped that this study can be used as a study or information that can be used as a theoretical basis for further research in job demand and job resources models. Job resources and job demands can be distinguished by their respective roles. In job resources, for example, autonomy can help employees to organize and complete work comfortably and feedback can help employees improve work performance. Then social support from colleagues and mentors from supervisors can increase motivation and emotional support at work. On the other hand, job demands, such as workload, emotions, and physical demands, are things that exist in a job that can be tolerated by the role of job resources.